YAP-Mediated Mechanotransduction in Skeletal Muscle - Fischer, Martina; Rikeit, Paul; Knaus, Petra; Coirault, Catherine (Frontiers in Physiology, 2016)
Skeletal muscle is not only translating chemical energy into mechanical work, it is also a highly adaptive and regenerative tissue whose architecture and functionality is determined by its mechanical and physical environment. Processing intra- and extracellular mechanical signaling cues contributes to the regulation of cell growth, survival, migration and differentiation. Yes-associated Protein (YAP), a transcriptional coactivator downstream of the Hippo pathway and its paralogue, the transcriptional co-activator with PDZ-binding motif (TAZ), were recently found to play a key role in mechanotransduction in various tissues including skeletal muscle. Furthermore, YAP/TAZ modulate myogenesis and muscle regeneration and abnormal YAP activity has been reported in muscular dystrophy and rhabdomyosarcoma. Here, we summarize the current knowledge of mechanosensing and -signaling in striated muscle. We highlight the role of YAP signaling and discuss the different routes and hypotheses of its regulation in the context of mechanotransduction.